Kontradiksi Nubuatan Yeremia dan Hananya Sebagai Syarat Menguji Nubuatan Berdasarkan Yeremia 28:1-17 - Pattinaja, Aska Aprilano; Liling, Sifera Sampe; Harahap, Firdaus Rinto (Jurnal Lentera Nusantara, 2024)
This study examines the prophetic contradictions between Jeremiah and Hananiah, highlighting the prevalence of false prophets who delivered messages to please the king or for personal gain. The contrasting prophecies of disaster and salvation delivered by Jeremiah and Hananiah become the focal point for examining the criteria that can be used to test the authenticity of a prophecy. Using a qualitative approach based on a hermeneutical study of the prophetic literature, particularly in the sub-genres of prophecy of doom and prophecy of salvation, this study seeks to shed light on key insights for believers in discerning true prophecy. The results of this study underscore several important criteria for testing prophecy: first, true prophecy must be consistent with actual events, showing its fulfillment in reality; second, confirmation of the prophecy by another trusted prophet serves as an important validation of its authenticity; and third, true prophecy is characterized by its alignment with God's Word, rather than being motivated by deceptive intentions or personal gain. By establishing these criteria, this study equips believers with the knowledge and discernment necessary to evaluate the validity of prophetic messages.AbstrakStudi ini menggali kontradiksi kenabian antara Yeremia dan Hananya, menyoroti prevalensi para nabi palsu yang menyampaikan pesan untuk menyenangkan raja atau mendapatkan keuntungan pribadi. Nubuat bencana dan keselamatan yang kontras yang disampaikan oleh Yeremia dan Hananya menjadi titik fokus untuk menguji kriteria yang dapat digunakan untuk menguji keaslian sebuah nubuat. Dengan menggunakan pendekatan kualitatif berdasarkan pada studi hermeneutika literatur kenabian, khususnya dalam sub-genre nubuat bencana dan nubuat keselamatan, penelitian ini berusaha untuk menjelaskan wawasan kunci bagi orang percaya dalam membedakan nubuat yang benar. Temuan-temuan dari penelitian ini menggarisbawahi beberapa kriteria penting untuk menguji nubuat, yaitu pertama, nubuat yang benar harus selaras dengan kejadian yang sebenarnya, menunjukkan penggenapannya dalam kenyataan; kedua, konfirmasi nubuat oleh nabi lain yang terpercaya berfungsi sebagai validasi penting atas keasliannya; dan yang ketiga, nubuat yang benar dicirikan oleh keselarasannya dengan firman Tuhan, bukan dimotivasi oleh niat menipu atau keuntungan pribadi. Dengan menetapkan kriteria-kriteria ini, penelitian ini memperlengkapi orang-orang percaya dengan pengetahuan dan ketajaman yang diperlukan untuk mengevaluasi keabsahan pesan-pesan nubuat.